2017
DOI: 10.1371/journal.pone.0173036
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between decreased lower extremity muscle mass and knee pain severity in both the general population and patients with knee osteoarthritis: Findings from the KNHANES V 1-2

Abstract: ObjectiveTo identify the prevalence of and risk factors for knee pain and radiographic knee osteoarthritis (RKOA) and to investigate the relationship between decreased lower extremity muscle mass (DLEM) and knee pain severity.MethodsUsing data from the Korea National Health and Nutrition Examination Survey, 3,278 participants who were ≥50 years old and who underwent dual x-ray absorptiometry, plain knee radiographs and completed a knee pain questionnaire were enrolled. Lower extremity muscle mass (LEM) was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Aging-related muscle mass deterioration was identified to be associated with the severity of knee pain, 49 particularly in older women with radiographically mild KOA. 50 For mild KOA (K-L grade = 2), appendicular muscle mass relative to body weight was reported to be significantly lower in patients with knee pain than in those without knee pain, whereas no such difference was noted for moderate-to-severe KOA (K-L grade ⩾3).…”
Section: Discussionmentioning
confidence: 99%
“…Aging-related muscle mass deterioration was identified to be associated with the severity of knee pain, 49 particularly in older women with radiographically mild KOA. 50 For mild KOA (K-L grade = 2), appendicular muscle mass relative to body weight was reported to be significantly lower in patients with knee pain than in those without knee pain, whereas no such difference was noted for moderate-to-severe KOA (K-L grade ⩾3).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been reported that exercise for 2 days or more per week on nonconsecutive days significantly reduces LBP [ 4 ][ 5 ]. The relation of low skeletal muscle mass of the extremities to other musculoskeletal pain has been reported [ 9 ][ 20 ]. These reports have indicated that low muscle mass of the extremities is associated with knee pain [ 20 ] and neck or shoulder pain [ 9 ], but is not related to LBP.…”
Section: Discussionmentioning
confidence: 99%
“…The relation of low skeletal muscle mass of the extremities to other musculoskeletal pain has been reported [ 9 ][ 20 ]. These reports have indicated that low muscle mass of the extremities is associated with knee pain [ 20 ] and neck or shoulder pain [ 9 ], but is not related to LBP. To our knowledge, only one study analyzed the direct relationship between trunk muscle strength and LBP and showed the association between isometric and isokinetic extensor weakness and LBP [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of Sattler et al 35 and Wang et al 40 showed a significant difference in muscle cross section of the vastus medialis in painful compared with contralateral painless limbs. Also, Cheon et al investigated the relationship between decreased lower extremity muscle mass and knee pain intensity in both the general population and patients with knee osteoarthritis 41. They found that a decreased lower extremity muscle mass was an independent risk factor for knee pain and it was associated with increased pain intensity, regardless of radiographic knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…However, probably not only the reduced pain has a positive influence on the muscle cross section, but also the associated increased physical activity. An increased physical activity induces a hypertrophy of lower limb muscle, especially of vastus medialis, which positively affects reduction in the pain level and pain perception of the patients 35 41. Also stress and depression, which are often associated with chronic pain, can be positively affected by physical exercise,42 43 which further promotes the healing process.…”
Section: Discussionmentioning
confidence: 99%